Full Energy Spectra of Interface State Densities for n‐ and p‐type MoS2 Field‐Effect Transistors. (30th September 2019) - Fang, Nan; Toyoda, Satoshi; Taniguchi, Takashi; Watanabe, Kenji; Nagashio, Kosuke
Abstract: 2D materials are promising to overcome the scaling limit of Si field‐effect transistors (FETs). However, the insulator/2D channel interface severely degrades the performance of 2D FETs, and the origin of the degradation remains largely unexplored. Here, the full energy spectra of the interface state densities ( D it ) are presented for both n ‐ and p ‐ MoS2 FETs, based on the comprehensive and systematic studies, i.e., full rage of channel thickness and various gate stack structures with h ‐BN as well as high‐ k oxides. For n ‐MoS2, D it around the mid‐gap is drastically reduced to 5 × 10 11 cm −2 eV −1 for the heterostructure FET with h ‐BN from 5 × 10 12 cm −2 eV −1 for the high‐ k top‐gate. On the other hand, D it remains high, ≈ 10 13 cm −2 eV −1, even for the heterostructure FET for p ‐MoS2 . The systematic study elucidates that the strain induced externally through the substrate surface roughness and high‐ k deposition process is the origin for the interface degradation on conduction band side, while sulfur‐vacancy‐induced defect states dominate the interface degradation on valance band side. The present understanding of the interface properties provides the key to further improving the performance of 2D FETs. Abstract : The interfacial properties of both n ‐ and p ‐MoS2 field‐effect transistors with a wide thickness range and various gate stack structures are investigated. The full energy spectra of the interface state densities are extracted. The external strain dominates the interface at the conduction band side, while sulfur‐vacancy‐induced defect‐states dominate the valance band side.